Chemical composition of Cinnamomum species collected in Sarawak - Syaliza Abdul Hammid,; Zaini Assim,; Fasihuddin Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Cinnamomum species (Lauraceae) are well known for their fragrance and medicinal value. The essential oils of three Cinnamomum species (C. macrophyllum, C. crassinervium and C. griffithii) collected in Sarawak were obtained by hydrodistillation and analyzed by gas chromatograpy mass spectrometry (GC-MS). The analysis of the oils showed that most of the essential oils were mainly phenylpropanoids and monoterpenes with a small amount of sesquiterpenes present. Both C. griffithii and C. crassinervium contained similar major chemical composition such as β-linalool, methyl cinnamate and eugenol methyl ether. No presence of methyl cinnamate and β-linalool were found in the oil of C. macrophyllum. m-Eugenol was prominent in the leaf oil of C. macrophyllum, while cinnamaldehyde was found mainly in the bark oil of C. macrophyllum. High percentage of camphor was identified in the bark and root oil of C. macrophyllum, compared to small amount of camphor found in the both root oil of C. griffithii and C. crassinervium.